2009
DOI: 10.1017/s0007485309990319
|View full text |Cite
|
Sign up to set email alerts
|

Within-field damage and distribution patterns of the stalk borer, Eldana saccharina (Lepidoptera: Pyralidae), in sugarcane and a comparison with nematode damage

Abstract: The occurrence of Eldana saccharina (Lepidoptera: Pyralidae) was monitored in grids represented by plots in 12 nematicide trials in South African sugarcane fields. The trials encompassed a total of eight plant cane crops and 22 ratoon crops and were situated within commercial cane fields. Several measurements were made to characterize the damage caused by E. saccharina. These included the number of internodes per stalk, the percentage of internodes damaged and the percentage of stalks damaged. The mapping of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…These results correspond to those of diffusion-type models such as that employed by Potgieter et al (2013), whereas the results shown in Figure 9 employ a larger number of "far flying" females, resulting in a flatter, more erratic distribution of the population. These results correspond with the observations of Berry et al (2010) who reported that, in experiments monitoring E. saccharina damage in sugarcane crops, the borders of the trial areas indicated infestation levels equal to those of the central areas. Berry also identified F I G U R E 1 0 Unbiased dispersion of a population different levels of infestation between adjacent stalks, resulting in a clustered arrangement of high and low areas of infestation across the field, dissimilar to the "diffusion-like" dispersal observed in the case of Figure 8.…”
Section: Sensitivity Analysis and Parameter Variationsupporting
confidence: 91%
See 1 more Smart Citation
“…These results correspond to those of diffusion-type models such as that employed by Potgieter et al (2013), whereas the results shown in Figure 9 employ a larger number of "far flying" females, resulting in a flatter, more erratic distribution of the population. These results correspond with the observations of Berry et al (2010) who reported that, in experiments monitoring E. saccharina damage in sugarcane crops, the borders of the trial areas indicated infestation levels equal to those of the central areas. Berry also identified F I G U R E 1 0 Unbiased dispersion of a population different levels of infestation between adjacent stalks, resulting in a clustered arrangement of high and low areas of infestation across the field, dissimilar to the "diffusion-like" dispersal observed in the case of Figure 8.…”
Section: Sensitivity Analysis and Parameter Variationsupporting
confidence: 91%
“…The model was verified and validated using standard techniques, and a face validation and parameter variation analysis were conducted. By establishing appropriate parameter values for particular configurations, the simulation model is capable of simulating a number of different scenarios, in particular, resulting in population dispersal similar in shape to those achieved by Potgieter et al (2013) and those observed in the field by Berry et al (2010). A simplified control measure was then implemented using the model in order to illustrate the manner in which it may be employed for control measure design and development going forward.…”
Section: Resultsmentioning
confidence: 99%
“…The plants with the highest growth potential attract lepidopteran pests. This attractive behavior of pests is mostly affected by the plants' nitrogen concentration [31]. High nitrogen supply usually increases protein production and decreases carbohydrates, so plants have softer tissue, and they are more susceptible to the ECB attack [32].…”
Section: The Role Of Nitrogen and C/n Ratio On The Intensity Of The Ecb Attackmentioning
confidence: 99%
“…E. saccharina damages affect young and adult cane stakes (as opposed to that of other stem borer species like S. calamistis, Chilo partellus and C. sacchariphagus on young tillers) increase with crop age, especially over 12 to 16 months of vegetation [7]. Insecticides were recently used in South Africa to control stem borer damages on reported sugarcane crops as a result of the closing of sugar mills during the summer [8]. Nevertheless, that practice was not unanimously adopted by growers because of the negative impact of pesticides on stem borer natural enemies.…”
Section: Introductionmentioning
confidence: 99%